Performance of maximum power point tracking by using conventional and soft computing techniques during partial shading conditions - Mahdi, Ammar Salah (2019)
Characteristics curves of solar module represent the characteristic of particular photovoltaic (PV) module. These curves reveal the ability of a specific solar module conversion and efficiency to extract maximum available power. In this study, the MSX-64 PV module and boost DC/DC converter are used for simulation and modeling the maximum power point tracking system. Maximum power extraction from PV system can be achieved by using maximum power point tracking (MPPT) techniques that are classified into conventional and soft computing. This work demonstrates the performance of three types of MPPT techniques for the PV system during partial shading conditions (PSC), where 25% and 50% shaded weather profile applied to the system. The system also subjected to a non-shaded real weather profile to examine the proposed MPPTs performance under changing weather conditions. The techniques used are fuzzy logic (FL) and adaptive neuro-fuzzy inference system (ANFIS) as soft computing technique which are compared with the conventional perturb and observe technique. The performance has evaluated under the same conditions of irradiance and atmospheric temperature by using the same operating conditions. These MPPT techniques are compared in terms of power extracted, MPPT efficiency, rise time, steady-state oscillation, its ability to track global maximum power point and the response to a varied weather. Simulation results of soft computing MPPT techniques have shown the ability to track the maximum power point during partial shading conditions and the response to weather changes when non-shaded real weather profile applied to the system. The performance of the conventional perturb and observe based MPPT has depicted the failure of this controller to track the global maximum power point during partial shading and lack response to real weather changes. The proposed system has implemented by using MATLAB/SIMULINK environment.